Salvage hepatectomy for local recurrence after particle therapy using proton and carbon ion beams for liver cancer. Issue 5 (7th May 2021) - Tanaka, Motofumi; Komatsu, Shohei; Kido, Masahiro; Toyama, Hirochika; Tominaga, Masahiro; Uchida, Yoichiro; Terashima, Kazuki; Demizu, Yusuke; Okimoto, Tomoaki; Fukumoto, Takumi
Abstract: Aim: With the increased use of particle therapy for liver cancer, local recurrence after particle therapy increased. Salvage hepatectomy is an acceptable treatment option for local recurrence following particle therapy; however, its safety and effectiveness remain unclear. Therefore, this multi‐center study aimed to verify the feasibility and efficacy of salvage hepatectomy and assess clinical issues associated with its application. Methods: We retrospectively assessed the perioperative outcomes, prognosis, and pathological characteristics of 15 patients who underwent salvage hepatectomy for local recurrence after particle therapy between 2006 and 2019. Results: Hepatocellular carcinoma and metastatic liver tumors were noted in eight and seven patients, respectively. The mean total dose and number of fractions were 66.5 Gy and 12, respectively, and the mean interval between particle therapy and surgery was 30.1 months. Major hepatectomy was performed in seven cases. Moreover, the mortality rate was 0%, and surgical complications of Clavien‐Dindo grade IIIa or higher were observed in four cases (27%)—two bile leakages, one pleural effusion, and one refractory skin fistula. The median overall survival time and 5‐year overall survival rate after salvage hepatectomy were 29.9 months and 43.1%, respectively. Histological examination of the irradiated liver tissue surrounding the tumor showed sinusoidal dilatation, loss of hepatocyte, and fibrosis in most cases. Conclusion: Salvage hepatectomy after particle therapy is a feasible therapy; however, the risk of refractory complications associated with particle therapy is relatively high. Therefore, the first‐line treatment for resectable liver cancer should be carefully determined considering second‐line treatment after local recurrence. Abstract : This is the first study that verified feasibility and efficacy of salvage hepatectomy for local recurrence after particle therapy and indicated clinical issues and pathological features of this therapy. These data would be a guidepost for surgeons to treat such patients.